Phytotoxicity of halloysite nanotubes using wheat as a model: seed germination and growth. Issue 10 (6th September 2021) - Chen, Linhong; Guo, Zizheng; Lao, Biyin; Li, Chunlei; Zhu, Jianhua; Yu, Rongmin; Liu, Mingxian
Abstract : Exposure of wheat to commercially available halloysite nanotubes at various concentrations (0.1 to 100 mg mL −1 ) results in an initial increase in crop growth, followed by certain phytotoxicity at high concentration. Abstract : Due to their special structure and biocompatibility, halloysite nanotubes (HNTs) have critical applications in polymer composites, drug delivery, waste treatment, and cosmetics. With the advance of industrial products based on HNTs and agrochemical carriers, it is urgent to study their phytotoxicity. Here, the influence of HNTs on the germination and growth of plants using wheat seeds as a model was investigated. The biomass, chlorophyll content and oxidative damage index of the HNT treated wheat group were compared with the control. HNTs have no significant effect on the germination of wheat seeds. The biomass (root/shoot length, and fresh weight) of the wheat treated with different concentrations of HNTs increased at doses of 0.1, 1, and 10 mg mL −1, while it decreased significantly at high concentrations of HNTs (100 mg mL −1 ). The chlorophyll content and oxidative damage index (cell membrane permeability, H2 O2 content, malondialdehyde content) increased with HNT concentration. A large accumulation of HNTs on the root sections was found in the high concentration HNT group, while no HNTs were observed in the xylem. Furthermore, HNTs can slightly decrease the viability of tobacco cells and promote the accumulation of biomass and secondary metabolites. This work demonstrated that HNTs at a certain concentration are safe to plants, while they are harmful at a high dose of 100 mg mL −1 . The understanding of the phytotoxicity of HNTs is helpful for their applications in the environmental protection and agricultural field.